ANALISIS EFEK DUKUNGAN SOSIAL, BUDAYA ORGANISASI, DAN KOHESIVITAS KARYAWAN TERHADAP LOYALITAS KARYAWAN (Studi pada RS. Aisyiyah Kudus) - Wazzar Achmad, Affan; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2018)
Employee loyalty can be recognized as one of the components that are needed by the organization. Employee loyalty has an impact on the psychological condition of each employee by giving loyalty to the organization. This study aims to examine and analyze the effects of social support, organizational culture, and employee cohesiveness on employee loyalty of Aisyiyah Kudus Hospital by using independent variables such as social support, organizational culture, and employee cohesiveness, as well as the dependent variable of employee loyalty.This research was conducted by survey method and through questionnaires to employees using random sampling method as many as 85 people. This study uses SPSS Statistics 21 software analysis tool. The data tests used include validity test, reliability test, classic assumption test, t test, F test, coefficient of determination (R2) and multiple linear regression analysis.The results of this study indicate that social support has a positive and significant impact on employee loyalty, organizational culture has a positive and significant impact on employee loyalty, and employee cohesiveness has a positive and significant impact on employee loyalty.